Enhanced bioethanol production from different sugarcane bagasse cultivars using co-culture of Saccharomyces cerevisiae and Scheffersomyces (Pichia) stipitis. Issue 3 (June 2017) - Santosh, Ingle; Ashtavinayak, Paradh; Amol, Dudhane; Sanjay, Patil
Abstract: Second generation bioethanol production through enzymatic route has potential in Indian scenario as large quantity of lignocellulosic material is available. India is second largest country in sugarcane production. Sugarcane bagasse and trash are renewable by-products of sugar industry that can be promising source of lignocellulosic waste. Till date no studies have been reported on application of sugarcane bagasse from different cultivars for bioethanol production in Indian scenario. For optimal ethanol production from lignocellulosic raw material, composition and fermentation characteristics of the substrate are significant factors to be considered. In present study, bagasse samples from ten different Indian sugarcane cultivars were studied for improved bioethanol production. Co-fermentation using pentose and hexose sugar fermenting yeast strains was also investigated for improved production of ethanol along with application of high solid load pre-treatment method. Maximum ethanol production of 31.01 ± 0.34 g/L in fermenting broth was obtained for COM 11007 cultivar, while maximum fermentation efficiency of 77.92 ± 0.88% was obtained for COM 11004. Final ethanol concentration in fermenting broth showed direct relation with initial concentration of fermentable sugar present. The present study demonstrates potential of mixed fermentation using Saccharomyces cerevisiae (VSI 1011) and Scheffersomyces (Pichia) stipitis (NCIM 3498) at high solid load of 16% (w/v) for enhanced ethanol production from the studied sugarcane bagasse cultivars.